Some preliminary conjunctural thoughts on countercultures - Grossberg, Lawrence (Wydawnictwo Naukowe UAM, 2014)
The article is devoted to analysis of various countercultures aspects. The Author hypothesizes that the forms of contemporary politics are the result of two fundamentally interrelated strategic vectors. First is built upon a politics of ressentiment, setting “ordinary” folks against the socio‐cultural elite which constututed to the “new right” movement. Second vector is originated of counterculture of the 1960s. The author states that counterculture exists without a singular identity. It is a space of hybridity and heterogenity. On the other hand counterculture is related to the concept of contemporary ambivalence as well it transforms of affective experience of everyday life. Another feature of counterculture is connected with the conviction that counterculture stands against of dominant culture. Also the author puts counterculture movements against various aspects of new american modernity including reconstruction of the practice of the hegemony, as well as through popular culture and reconstruction of the „left” and „right” idelogy and practice.
Keywords: counterculture; hegemony; „left”; „right”; popular culture; American modernity